IMPLEMENTASI ALGORITMA HITS PADA APLIKASI MESIN PENCARI (SEARCH ENGINE) BERBASIS JAVA - Cecep Juliansyah; Muhsin .; Sandy Wibawanto (NUANSA INFORMATIKA, 2010)
Internet has grown rapidly into a commercial transaction media and warehouses of all sorts of information. The amount of data and information in the Internet continues to grow bigger and thus require the means and the specific ways in order to access the information more efficiently and effectively. Currently there are about hundreds of millions of web pages on the internet and will continue to grow each day. Whereas in fact, that some information on the internet is not the information that is really appealing to Internet users. Therefore emerging web search algorithms are complex. One of them is a web search algorithm based on link analysis. The objective of this paper is to make an application for a search engine intended to search the relevant so that the results are expected to provide relevant web pages in accordance with the wishes of the user.Keywords: Search Engines, Relevance, Hyperlink Induced Topic Search (HITS), Authority,Hub